2009
DOI: 10.1038/jhg.2009.96
|View full text |Cite
|
Sign up to set email alerts
|

Replication of CD58 and CLEC16A as genome-wide significant risk genes for multiple sclerosis

Abstract: Description Functions for simple fixed and random effects meta-analysis for two-sample comparisons and cumulative meta-analyses. Draws standard summary plots, funnel plots, and computes summaries and tests for association and heterogeneity.Title Meta-AnalysisLicense GPL-2Imports grid, stats, graphics Examples library(rmeta) data(catheter) a <-meta.MH(n.trt, n.ctrl, col.trt, col.ctrl, data=catheter, names=Name, subset=c (13,6,5,3,7,12,4,11,1,8,10,2)) b <-meta.DSL(n.trt, n.ctrl, col.trt, col.ctrl, data=catheter,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 27 publications
0
39
0
1
Order By: Relevance
“…[4,5] Outside of the HLA region, interleukin 2 receptor alpha (IL2RA) and interleukin 7 receptor (IL7R) are two of the genes more consistently found associated with risk of MS. [6,7] A meta-analysis of IL2RA rs2104286 and IL7R rs6897932 have confirmed these associations in the Caucasian population, [8,9] including Canadian patients. [10] Interestingly, one study found IL7R rs6897932 to be exclusively associated with patients presenting primary progressive MS (PPMS) and secondary progressive MS (SPMS), suggesting IL7R may have an effect on the development of a progressive disease course. [11] To further elucidate the role of IL2RA and IL7R in MS pathogenesis and disease course, we genotyped rs2104286 and rs6897932 in a large Canadian case-control series consisting of 1,978 MS patients and 830 controls, and sequenced the entire coding region for each gene in 95 MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…[4,5] Outside of the HLA region, interleukin 2 receptor alpha (IL2RA) and interleukin 7 receptor (IL7R) are two of the genes more consistently found associated with risk of MS. [6,7] A meta-analysis of IL2RA rs2104286 and IL7R rs6897932 have confirmed these associations in the Caucasian population, [8,9] including Canadian patients. [10] Interestingly, one study found IL7R rs6897932 to be exclusively associated with patients presenting primary progressive MS (PPMS) and secondary progressive MS (SPMS), suggesting IL7R may have an effect on the development of a progressive disease course. [11] To further elucidate the role of IL2RA and IL7R in MS pathogenesis and disease course, we genotyped rs2104286 and rs6897932 in a large Canadian case-control series consisting of 1,978 MS patients and 830 controls, and sequenced the entire coding region for each gene in 95 MS patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another GWAS subsequently performed by the Australian and New Zealand MS Genetics Consortium 11 confirmed some of the genes previously found, such as IL7R, IL2RA, EVI5-RPL5, CLEC16A or CD58, which have been consistently validated in independent studies. [11][12][13] Another GWAS was conducted in 1000 MS patients and an age/gender-matched control group. 14 In contrast to the International MS Genetics Consortium study, the latter focused on the discovery of genes not only associated with MS susceptibility, but also with the clinical phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…rs6897932 genotyping was performed as previously described with either a Sequenom platform (16) or TaqMan assay (17). Both MS patients (p = 0.98) and HC (p = 0.89) were in Hardy-Weinberg equilibrium.…”
Section: Genotypingmentioning
confidence: 99%